(untitled) (Journal of Forensic Medicine & Toxicology, 2015)
Self-inflicted injury is defined as the intentional and direct injuring of body tissues most often without suicidal intentions. Self-inflicted injuries show characteristic features which can be used to distinguish them from injuries inflicted by third parties. Various forms of self inflicted injuries are encountered in hospital settings such as Biting, self immolation by burning, incised wounds with sharp objects such as knives, needles, razor blades, scissors, pins, fingernails, etc. or Poisoning or drug over dosage. The paper discusses in detail common characteristics of self inflicted injuries and their Forensic implications.